2017
DOI: 10.1002/chem.201701587
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Mediated [4+2] Annulation of N‐Cyclobutylanilines with Alkynes Catalyzed by Self‐Doped Ti3+@TiO2

Abstract: We herein report a visible light mediated heterogeneous [4+2] annulation of N-cyclobutylanilines with alkynes catalyzed by self doped Ti3+@TiO2. The self doped Ti3+@TiO2 is stable under photooxidation conditions, easy to recycle, and can be used multiple times without appreciable loss of activity. Extensive mechanistic studies suggest that the annulation reaction is mediated by singlet oxygen that is generated via photosensitization of oxygen in the air by the self doped Ti3+@TiO2. In contrast, the homogeneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 72 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…The requirement for a sequential ring-opening and nucleophile addition is due to the incompatibility of many nucleophiles with highly oxidizing reaction conditions. In many cases, successful extension to aminocyclobutanes 33,34,[79][80][81] or nitrogen-substituted bicyclo[1.1.1]-pentanes 82 has been realized for synthesizing building blocks by a (4+2) annulation or a 1,4-difunctionlization reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for a sequential ring-opening and nucleophile addition is due to the incompatibility of many nucleophiles with highly oxidizing reaction conditions. In many cases, successful extension to aminocyclobutanes 33,34,[79][80][81] or nitrogen-substituted bicyclo[1.1.1]-pentanes 82 has been realized for synthesizing building blocks by a (4+2) annulation or a 1,4-difunctionlization reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Zheng and Feng reported that when the photocatalyst was replaced by self-doped Ti 3+ @TiO 2 , the same reaction proceeded very well with a comparable substrate scope, and the photocatalyst can be reused multiple times without an obvious decrease in the catalytic activity. 113 Later, the Zheng group disclosed an interesting visible lightdriven synthesis of substituted naphthalenes 117 via the [4 + 2] annulation of aminobenzocyclobutenes 116 and alkynes 112 (Scheme 35). 114 A variety of terminal alkynes, internal alkynes, and diynes were suitable for this transformation, affording corresponding products 117 in high yields.…”
Section: Aminium Radical Cation-mediated C−c Bond Cleavagementioning
confidence: 99%